KAJIAN KONSEPTUAL TENTANG LIMIT FUNGSI SEBAGAI FONDASI PEMBELAJARAN KALKULUS - Aferbina Br Barus; Fasya Maharani Umri; Nur Hidayah Aini; Tiur Malasari Siregar (Universitas Batanghari Jambi, 2026)
This study aims to examine the basic concept of function limits in calculus and analyze their vital role as the main foundation in learning calculus. The research method employed is a literature review, analyzing various sources such as textbooks and scientific journal articles related to limit concepts, student misconceptions, and relevant pedagogical strategies. Data analysis was conducted qualitatively and descriptively to synthesize the relationship between the concept of limits, derivatives, and integrals. The results indicate that the limit is a fundamental concept that explains functional behavior and serves as the formal basis for defining derivatives as rates of change and integrals as area accumulation (Riemann sums). The study concludes that a strong conceptual understanding of limits is essential to avoid the dominance of mechanistic procedures and to help students master advanced calculus concepts systematically. It is suggested that calculus instruction should emphasize visual representation and mathematical interpretation, although this study is limited to a literature approach without empirical field data.